Management of safe behavior to maintain life at the Brazilian Antarctic Station - Paola Barros-Delben; Roberto Moraes Cruz; Gabriel de Melo Cardoso; Daniela Ornellas Ariño; Gustavo Klauberg Pereira; Mariana Lopez (Revista Psicologia)
In polar regions, the management of safe behavior is fundamental to supply operations to maintain life (OPML). The objective of this study was to control OPML at the Comandante Ferraz Antarctic Station during the winter. The research was descriptive, with a qualitative approach and the procedure of triangulation of observations and survey. Routine questions and interviews with the crew (n = 12) and with the base group (BG) of Ferraz Station (N = 30) were conducted. The autonomy of the BG in the work minimizes the impact of extreme winter characteristics. OPML at Ferraz Station has direct repercussions on subsistence and on the maintenance of external affective bonds. The study of safe behavior points to factors with the potential to reduce the risks of accidents and illness, having impact on healthy permanence in this context. Improvement of these studies can contribute to attending to human factors in polar conditions.